A Cross-Sectional Study of Empathy and Emotion Management: Key to a Work Environment for Humanized Care in Nursing - Pérez-Fuentes, María del Carmen; Herrera-Peco, Ivan; Molero Jurado, María del Mar; Oropesa Ruiz, Nieves Fátima; Ayuso-Murillo, Diego; Gázquez Linares, José Jesús (Frontiers in Psychology, 2020)
Introduction At the present time, technological advances have increased the technification of healthcare services, in which high priority is given to efficiency and results achieved, leading healthcare personnel to prioritize administrative and procedural aspects to the detriment of humanization of care and the work environment. Objective This study was intended to continue progress in research on the work environment based on the humanization construct by analyzing the explanatory value of emotional intelligence and empathy in nursing personnel. Materials and Methods The study was quantitative, observational, and cross-sectional. The sample was made up of 338 Spanish nurses with a mean age of 32.20 (SD = 7.54; range 22–56). The instruments employed for analysis were the Healthcare Professional Humanization Scale (HUMAS), Brief Emotional Intelligence Inventory for Adults, and Basic Empathy Scale (BES). Results Mood and stress management—both emotional intelligence components—and cognitive empathy explained over half (51%) of the variability found in humanization of care in a sample of nurses. Furthermore, the mediation models proposed emphasized the mediating role of cognitive empathy in stress management and improvement in mood and its relationship to humanization. Conclusion It is recommended that healthcare professionals reinforce their personal competencies in order to tend to the needs of their patients empathetically and improve emotional competencies for coping successfully with potentially stressful situations.